Experimental Investigation of Seismic Parameters and Bearing Capacity of Pavement Subgrade Using Surface Wave Method - Wahyu Widodo; Sri Atmaja P Rosyidi (Universitas Muhammadiyah Yogyakarta, 2009)
The spectral analysis of surface waves (SASW) method is introduced as an in-situ non-destructive seismic technique where the method consists of the generation, measurement and processing the dispersive Rayleigh waves from two vertical transducers. Subsequently, the dispersive data of Rayleigh phase velocity are inverted and the shear wave velocity versus depth of the site is obtained. The dynamic stiffness parameters, i.e. elastic modulus generated from the SASW measurements are at a very small strain levels of 0.001%. At this strain level the soil is linearly elastic and the use of elastic theories is thus justified. The aim of this paper is to investigate the seismic parameters of the pavement subgrade stiffness using the SASW method and to predict its bearing capacity based on the seismic parameters. In order to determine the bearing capacity, in situ dynamic cone penetrometer (DCP) was also carried out in the same location of SASW test. The relationship of the shear wave velocity and dynamic elastic modulus (Edynamic) of the SASW were found to be in good correlation with bearing capacity obtained by the DCP.